Biomineralization of calcium carbonate in bioconcrete by the action of Bacillus subtilis ATCC 6633 - Rodrigues dos Santos, Júlio (2025)
In this study, the viability of bacterium Bacillus subtilis (ATCC 6633) as a biological agent in the process of precipitation of calcium carbonate (CaCO3) on the surface of concrete was investigated. This evaluation was first carried out in a curing tank for concrete samples, using a nutrient solution enriched with B. subtilis for comparison with control samples without the addition of microorganisms. The biomineralized samples with B. subtilis showed a 21.01% reduction in void content and a 25.31% reduction in water absorption by capillarity. Due to the surface protection, the microorganisms reduced the porosity of the material, resulting in an increase in compressive strength of about 6.41%. The mineral morphologies analyzed by SEM included cubic, polygonal and rhombohedral crystals. Chemical evaluation by EDX and characterization by XRD of the bioconcretes indicated the presence of CaCO3 precipitated by the bacteria. The results obtained show that the superficial application of B. subtilis (ATCC 6633) on concrete leads to an improvement in mechanical and durability properties.